2019
DOI: 10.1109/tgcn.2018.2876005
|View full text |Cite
|
Sign up to set email alerts
|

Renewable Energy Sharing Among Base Stations as a Min-Cost-Max-Flow Optimization Problem

Abstract: Limited work has been done to optimize the power sharing among base stations (BSs) while considering the topology of the cellular network and the distance-dependent power loss (DDPL) in the transmission lines. In this paper, we propose two power sharing optimization algorithms for energy-harvesting BSs: the max-flow (MF) algorithm and the min-cost-max-flow (MCMF) algorithm. The two proposed algorithms minimize the power drawn from the main grid by letting BSs with power surpluses transmit harvested power to BS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…is algorithm is well-known and widely used in cloud resource allocation [38], energy sharing management [39], resource management [40,41], and network traffic management [42,43].…”
Section: Relocation Optimizationmentioning
confidence: 99%
“…is algorithm is well-known and widely used in cloud resource allocation [38], energy sharing management [39], resource management [40,41], and network traffic management [42,43].…”
Section: Relocation Optimizationmentioning
confidence: 99%
“…For each work in more detail, D. Niyato et al [123] investigated the performance of a solar-powered wireless sensor/mesh network in terms of packet blocking and dropping probabilities with the presented queuing model. Given the fact that as the period of BS's off state increases, the packet blocking probability also increases while the packet dropping [95], [113], [114] [82], [100], [102] [103], [115] [84], [95], [100], [103] [107], [114] [38], [79]- [81] [84], [88], [89] [107] [116], [117] Minimizing the total energy (on-grid and RE) cost [118] Minimizing the net energy cost in smart grid [21] Maximizing the network utility [55], [99], [101] [76], [99] [76] Minimizing the network latency [39], [85] [57], [58] Maximizing the weighted sum of on-grid consumption and user QoS metric [40] [40], [41] [42]- [44] [86], [87], [108] [41], [108] Maximizing the utilization of RE [104] [82], [104] Maximizing the energy efficiency [96], [105] [47], [105] Minimizing the cost of using conventional energy source [106] [83], [93] [36], [37], [91] [6...…”
Section: Design and Optimization Issuesmentioning
confidence: 99%
“…The regarding works determine the amount of wired energy transaction among the BSs or between BS and smart grid or both. With the optimal amount, grid power consumption can be minimized [89], [107], [116], [117]. In the case of energy sharing through physical power line between two BSs, it was shown that 80% of grid power consumption can be saved [89].…”
Section: Bs Cooperation 1) Coordinated Multipoint (Comp)mentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of solar power generation is may be higher or lower in accordance with tempo-spatial traffic diversity and solar radiation intensity which often causes a mismatch with the BS load consumption. The concept of sharing surplus electricity among neighboring BSs via smart grid or external physical transmission lines has been recognized as an emerging solution in some literature [26]- [28]. An efficient energy cooperation framework among collocated BSs via smart grid based on the level of a priori knowledge about RE generation has been proposed in [28].…”
Section: Introductionmentioning
confidence: 99%